Incidence of Primary Central Nervous System Tumors Among the Hispanic Population in Texas 1995-2013 - Ambe, Solomon (Cureus, 2020)
Introduction: Primary central nervous system (CNS) tumors constitute a group of rare and heterogeneous tumors. A rising incidence rate in the United States has been linked to modern changes in early diagnosis and reporting. This study aims to examine temporal incidence trends, geographic variation, and the average annual age-adjusted rates among Hispanic populations in Texas from 1995 to 2013. Methods: SEER*STAT (Surveillance Research Program, National Cancer Institute (seer.cancer.gov/seerstat) version 8.3.2) and Joinpoint Regression 4.4.0.0 (Statistical Methodology and Applications Branch, Surveillance Research Program, National Cancer Institute) software were used to analyze incidence of primary brain and CNS tumors among Texas residents. Data were obtained from the Texas Cancer Registry of the Texas Department of State Health Services. Results: From the 30,122 cases of primary CNS tumors diagnosed throughout the state of Texas from 2008 to 2012, the overall average annual age-adjusted incidence rate for Hispanics and non-Hispanics combined was 25.35 per 100,000 persons. Among Hispanics, West Texas had the highest incidence trends and the highest average age-adjusted incidence rate of 27.17, followed by North Texas at 26.01 and the Panhandle at 23.63. East Texas had the lowest incidence rate of 16.23. The incidence trend among Hispanics has decreased consistently at a rate of 0.83 % from 1995 to 2013. Conclusions: The incidence of tumors was more pronounced in the Hispanic population in northern Texas compared with southern Texas. The presence of oil and gas production industries with farming and construction could play a role in the observed incidence of disease. Further studies with a focus on occupational health among Hispanics in Texas will be needed to elucidate the cause of such distribution.